2021
DOI: 10.1055/a-1525-2588
|View full text |Cite|
|
Sign up to set email alerts
|

Islet Co-Expression of CD133 and ABCB5 in Human Retinoblastoma Specimens

Abstract: Background The role of CD133 und ABCB5 is discussed in treatment resistance in several types of cancer. The objective of this study was to evaluate whether CD133+/ABCB5+ colocalization differs in untreated, in beam radiation treated, and in chemotherapy treated retinoblastoma specimens. Additionally, CD133, ABCB5, sphingosine kinase 1, and sphingosine kinase 2 gene expression was analyzed in WERI-RB1 (WERI RB1) and etoposide-resistant WERI RB1 subclones (WERI ETOR). Methods Active human untreated ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…To identify the mechanisms of chemotherapy resistance, the etoposide-resistant subclone WERI-ETOR was established by harvesting surviving cells after incubation with increasing etoposide doses from WERI-RB1, as described by Stephan et al [ 12 ]. Previous studies also examined the parental WERI-RB1 and the etoposide-resistant subclone WERI-ETOR on the molecular level [ 13 , 14 , 15 , 16 , 17 , 18 ]. Furthermore, Busch et al demonstrated a higher proliferation rate in WERI-ETOR as well as increased tumor formation and tumor size in an in vivo chick chorioallantoic-membrane assay [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…To identify the mechanisms of chemotherapy resistance, the etoposide-resistant subclone WERI-ETOR was established by harvesting surviving cells after incubation with increasing etoposide doses from WERI-RB1, as described by Stephan et al [ 12 ]. Previous studies also examined the parental WERI-RB1 and the etoposide-resistant subclone WERI-ETOR on the molecular level [ 13 , 14 , 15 , 16 , 17 , 18 ]. Furthermore, Busch et al demonstrated a higher proliferation rate in WERI-ETOR as well as increased tumor formation and tumor size in an in vivo chick chorioallantoic-membrane assay [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…To identify the mechanisms of chemotherapy resistance, the etoposide resistant subclone WERI ETOR was established by harvesting surviving cells after incubation with increasing etoposide doses from WERI RB1 as described by Stephan et al (12). Previous studies also examined the parental WERI RB1 and the etoposide resistant subclone WERI ETOR on the molecular level (13)(14)(15)(16)(17)(18). Furthermore, Busch et al demonstrated a higher proliferation rate in WERI ETOR as well as an increased tumor formation and tumor size in an in vivo chick chorioallantoic membrane assay (17).…”
Section: Introductionmentioning
confidence: 99%